'All-things-considered, ' 'Better-than, ' And Sports Rankings. Issue 2 (3rd May 2016) - Bordner, S. Seth
Abstract : Comparative judgments abound in sports. Fans and pundits bandy about which of two players or teams is bigger, faster, stronger, more talented, less injury prone, more reliable, safer to bet on, riskier to trade for, and so on. Arguably, of most interest are judgments of a coarser type: which of two players or teams is, all-things-considered, just plain better ? Conventionally, it is accepted that such comparisons can be appropriately captured and expressed by sports rankings. Rankings play an important role in sports arguably because of the conventional acceptance that rankings capture and express all-things-considered relations between the ranked teams or players. Standard ranking practices rely on a number of widely held assumptions. I discuss three of the most important and argue that at least one of them must be false. If this is right, the strong and growing commitment to using rankings to determine participation in tournaments and the awarding of championships is mistaken. At the least, given the conventional wisdom about rankings, my argument provides good reasons to be skeptical that any particular ranking 'gets it right'. At the limit, it suggests that our most basic assumptions about all-things-considered athletic quality are wrong.